ETIKA PENDIDIK DALAM PERSPEKTIF AL QURAN DAN HADITS - -rovi. amelia rovi ramadhani (AL-IBANAH, 2026)
This research is crucial given the strategic role of educators in shaping the character and morals of future generations, who are currently faced with increasingly complex modern challenges. This study aims to identify and analyze specific verses from the Quran and Hadith—namely Surah At-Taubah: 128, Surah Al-An'am: 162–163, Surah Ali 'Imran: 164, and the Hadith narrated by Jabir bin Abdullah—regarding the ethical foundations of educators, and to evaluate their application in the modern education system. Utilizing a qualitative library research method, this study explores primary Islamic texts alongside secondary academic references from the last ten years. The results indicate that an ideal Islamic educator must possess core ethical values: a deep sense of empathy and dedication to student welfare, a total theological commitment (ikhlas), and a pedagogical mission focused on purification (tazkiyah), intellectual development, and making learning accessible (taysir). Integrating these prophetic ethical principles serves as a crucial moral foundation for reforming modern educational practices, ensuring that students develop not only academic intelligence but also profound moral character and social responsibility.